Guru Honorer dan Stagnasi Mutu Pendidikan Indonesia dalam Perspektif Sejarah (1900-2026) - Kurniawan; Siti Fatimah (Universitas Insan Budi Utomo, 2026)
The honorary teacher crisis in Indonesia has been ongoing for decades without a fundamental solution. This article aims to analyze the historical-structural roots of the honorary teacher problem and its correlation with the stagnation of national education quality. This research employs historical methods with a qualitative approach through four stages: heuristics, source criticism, interpretation, and historiography. The theoretical frameworks used are Fernand Braudel's longue durée, Pierre Bourdieu's social reproduction, and Paulo Freire's critical pedagogy. The results show that the honorary teacher crisis is not merely a technical failure in implementing Law Number 14 of 2005 concerning Teachers and Lecturers, but an accumulation of three layers of structural inheritance: discriminatory dualism from the colonial era, the